Kepatuhan Pasien pada Program Therapeutic Community - 'Izzat, Muhammad Anwarul; Nurmala, Ira; Sulistyowati, Muji (Journal of Telenursing (JOTING), 2024)
This research aims to determine the factors that influence the compliance of drug abuse patients in participating in therapeutic community programs at social drug rehabilitation institutions. This research is a systematic journal using the preferred item reporting method for systematic and meta-analysis (PRISMA) from online databases. Therapeutic community programs in social drug rehabilitation institutions do not all run smoothly, so it is necessary to know the factors that influence the compliance of patients who are victims of drug abuse in participating in therapeutic community programs in social drug rehabilitation institutions. The results of this research show that the factors that influence patient compliance in participating in a therapeutic community program include family factors, a counselor's skills in interacting with counselors, economic factors, peer factors, environmental factors including social support, social relationships and social interactions. The conclusion of this research is that there are factors that influence patient compliance in participating in the therapeutic community program in social drug rehabilitation. Keyword: Adherence, Drug Abuse, Therapeutic Community